A new media access control layer quality of service multicast scheme for IEEE 802.11s-based wireless mesh networks. (1st January 2014) - Guesmia, Mohamed; Guezouri, Mustapha; Mbarek, Nader
We propose a new media access control (MAC) layer enabling quality of service (QoS) multicast scheme for IEEE 802.11s networks, where a unicast routing protocol called hybrid wireless mesh protocol (HWMP) is defined. The HWMP protocol is more adapted for best effort traffic that is why its usage is not suitable for real time multimedia applications. The goal of our proposed mechanism is to take into account multicast communication under QoS constraints for the IEEE 802.11s mesh networks where no QoS multicasting has been defined. Our multicasting scheme handles QoS guarantee for real time applications. Indeed, our scheme is based on finding the QoS multicast tree thanks to an end-to-end delay evaluation to cover multicast services. A QoS multicast tree is constructed based on the proactive tree HWMP mechanisms. Simulations results, using Network Simulator 3 (NS 3), show that our scheme improves data multicast transmission overhead as well as network throughput.